2009
DOI: 10.1021/jp9077079
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of Planar Boron Sheets: A New Template for Hydrogen Storage

Abstract: We study the hydrogen storage properties of planar boron sheets and compare them to those of graphene. The binding of molecular hydrogen to the boron sheet (0.05 eV) is stronger than that to graphene. We find that dispersion of alkali metal (AM = Li, Na, and K) atoms onto the boron sheet markedly increases hydrogen binding energies and storage capacities. The unique structure of the boron sheet presents a template for creating a stable lattice of strongly bonded metal atoms with a large nearest neighbor distan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(80 citation statements)
references
References 55 publications
9
70
0
1
Order By: Relevance
“…The previous research by Brocks et al. has revealed the potential of Li‐doped planar boron sheet in hydrogen storage, which reported a high gravimetric density of 10.7 wt% . However, the experimentally observed borophenes show three main structures (β 12 , χ 3 and striped borophene): the β 12 borophene and χ 3 borophene has planar structure with periodic holes, while striped borophene has buckled structure with anisotropic corrugation .…”
Section: Introductionmentioning
confidence: 99%
“…The previous research by Brocks et al. has revealed the potential of Li‐doped planar boron sheet in hydrogen storage, which reported a high gravimetric density of 10.7 wt% . However, the experimentally observed borophenes show three main structures (β 12 , χ 3 and striped borophene): the β 12 borophene and χ 3 borophene has planar structure with periodic holes, while striped borophene has buckled structure with anisotropic corrugation .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen boride exhibits a hexagonal boron network with bridged hydrogen atoms on the surface which can be used as a reducing agent like NaBH 4 . Besides, the planar borophene has been predicted to store hydrogen upto 10.7 wt% …”
Section: Synthesis Structure and Propertymentioning
confidence: 99%
“…Boron sheets, fullerenes, and nanotubes may be promising hydrogen storage media, since they are also light‐weight. Using first‐principles calculations, the buckyball B 80 coated with various metals M=Li, Na, K, Be, Mg, Ca, Sc, Ti, and V have been investigated for hydrogen storage 2527. It has been found that Na and Ca appear to be the best candidates for hydrogen storage.…”
Section: Introductionmentioning
confidence: 99%